ANALYSIS SERVICE QUALITY OF BPJS PHARMACY PT. MEDIKA ANTAPANI USING SERVQUAL AND KANO’S MODEL - Ismaya, Yunita Riska; Adhiutama, Akbar (Journal of Business and Management, 2018)
Abstract.Background Ã¢â‚¬â€œ The paper aims to help company to measure its customer satisfaction and identify which attribute should be prioritized for improvement through quantitative analysis of SERVQUAL and KanoÃ¢â‚¬â„¢s Model.Methods - Data was collected using survey amongst randomly selected individuals from BPJS Pharmacy PT. Medika Antapani customer. There are two questionnaires. The first questionnaire was intended to measure customer satisfaction and the second questionnaire was used to classify each attributes into Kano Category. Further analysis by combining the results of two questionnaires to determine which attributes should be prioritized for improvement.Results Ã¢â‚¬â€œ The result shows that there are 14 attribute of 16 attribute that has negative customer gap. It means that the customer expectation toward BPJS Pharmacy PT. Medika Antapani is higher than the perception. As for the attribute that should be prioritized for improvement according to Kano Category, there are 5 attributes that should be prioritized which are maintain speed and quality of service during busy time, provide enough seating for customer, employee always willing to help, employee have knowledge to answer question and polite and friendly employee.Conclusions Ã¢â‚¬â€œ For better improvement of BPJS Pharmacy PT. Medika Antapanishould prioritized must be requirement attribute for improvement as customer see the attribute as basic service. The next one is try to reduce the customer gap between customer expectation and perception by fulfilling one-dimensional attribute. And as for achieve competitive advantage, BPJS Pharmacy PT. Medika Antapanican more focus in attractive attribute.Keywords: customer satisfaction, Kano model, pharmacy service, service quality, SERVQUALÃ‚Â Ã‚Â Ã‚Â